The economic burden of treating uncomplicated hypertension in Sub-Saharan Africa: a systematic literature review - Gnugesser, Eva; Chwila, Claudia; Brenner, Stephan; Deckert, Andreas; Dambach, Peter; Steinert, Janina; Bärnighausen, Till; Horstick, Olaf; Antia, Khatia; Louis, Valérie R. (BMC public health, 2022)
Hypertension is one of the leading cardiovascular risk factors with high numbers of undiagnosed and untreated patients in Sub Saharan Africa (SSA). The health systems and affected people are often overwhelmed by the social and economic burden that comes with the disease. However, the research on the economic burden and consequences of hypertension treatment remains scare in SSA. The objective of our review was to compare different hypertension treatment costs across the continent and identify major cost drivers.
Gesehen am 27.10.2022